Awareness on the impact of disposable syringes re-use and benefits of Auto-disable (AD) syringes in health care professionals and students in Karachi, Pakistan - Tariq Ali,Princess Asmarah Shehzeb,Faryal Hanif,Hafsa Qureshi,Omema Owais,Sana Usmani,Madiha Batool,Falak Haider,Fawad Yousuf and Sara Arshad (Journal of Applied Pharmaceutical Science)
Karachi is the most advanced and populated city of Pakistan with approximately 20 million residents. The good health care practices awareness among health professionals especially use of syringes is an important role player for the control of disease spread by re-use of syringes. A quantitative approach involving a cross sectional survey based study, was carried out among four different categories of health personnel. A total of 200 participants were asked to fill a structured questionnaire (Doctors, Nursing staff, Lab technicians, and graduating health care students with a sample size of 50 for each group). A large proportion of participants were aware of the impact of re-use of disposable syringes and emphasized on the need for proper disposal system existence to eradicate the issue. The study results also showed that about 71 % of the health professionals had awareness on Auto-disable syringes use and around 29% had no knowledge about AD syringes. About 79 % of health care professionals agreed that AD syringe would reduce needle sharing and would help to cut down Hepatitis B, C and HIV.
Keywords: Disposable syringes,Auto-disable (AD) syringes,health care professionals,Karachi,Pakistan.